Method for monitoring thermal oxidative stability of transmission oil TAP-15V - B. I. Kovalskiy; V. I. Vereshchagin; V. G. Shram; E. G. Kravtsova; O. N. Petrov; M. A. Kovaleva (Омский научный вестник)
This paper presents the results of a study of the mineral transmission oil TAP-15V for the determination of thermal oxidative stability indicators including optical density, viscosity, and volatility. The effect of temperature on oxidative processes is shown. Thus, the study of thermo-oxidative stability using the optical form of non-destructive testing using the photometry method of oxidized gear oils allows us to evaluate the kinetics of changes in optical properties determined by the absorption coefficient of the light flux to determine the relationship between optical properties and viscosity, as well as the rate of oxidation processes and the volatility of oils, which allowed as a parameter of thermo-oxidative stability of oils to offer a complex coefficient of thermo-oxidative destruction, considering the optical properties and the viscosity at their oxidation.